Advanced accounting (Filmstrip) - Langer, Charles Heinrichs, 1876-1952.; Walton Publishing Company, Chicago. [from old catalog] (Charles Heinrichs Langer: Made and released by Walton Pub. Co., 1948)
Each film is composed of text frames which discuss various principles of accounting.
To accompany a lectures series of the same title.
Keywords: Accounting